2020
DOI: 10.1186/s13065-020-00711-4
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of polylactic acid/paclitaxel nano fibers by electrospinning for cancer therapeutics

Abstract: Polylactic acid (PLA) is a thermoplastic and biodegradable polyester, largely derived from renewable resources such as corn starch, cassava starch and sugarcane. However, PLA is only soluble in a narrow range of solvents such as tetrahydrofuran, dioxane, chlorinated solvents and heated benzene. The limited choices of solvent for PLA dissolution have imposed significant challenges in the development of specifically engineered PLA nanofibers with electrospinning techniques. Generally, the electrospun polymeric m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 42 publications
(28 reference statements)
1
15
0
Order By: Relevance
“…Figure 2 shows the FTIR spectra ranging from wavenumber 4000 cm −1 to 550 cm −1 . The small peaks at 2946.09 to 2996.32 cm −1 are attributed to the CH stretching vibration, and sharp absorption peaks at 1749.29 cm −1 belongs to the C=O stretching which can be observed in all samples [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows the FTIR spectra ranging from wavenumber 4000 cm −1 to 550 cm −1 . The small peaks at 2946.09 to 2996.32 cm −1 are attributed to the CH stretching vibration, and sharp absorption peaks at 1749.29 cm −1 belongs to the C=O stretching which can be observed in all samples [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…One disadvantage of using a second polymer to facilitate electrospinning is that the alginate concentration has been limited to 40% by weight. 46…”
Section: Polymersmentioning
confidence: 99%
“…There seems to be a large focus on specific areas where delivery for timely and targeted action is crucial such as anticancer delivery. Chemotherapeutics such as 5FU [352][353][354][355][356][357][358], doxorubicin [356,[359][360][361][362], paclitaxel [363][364][365][366], cisplatin [367][368][369] and metformin [370] have been used as model drugs to show the effectiveness of ES in cancer therapy. For example, Ghahreman et al fabricated 5FU-loaded PCL/gelatin fibers which showed by increasing the amount of gelatin in the composition; drug release increased [354].…”
Section: Electrospinningmentioning
confidence: 99%